Legal Consequences and Notary Responsibilities for The Hawalah Contract Deed That Does Not Meet The Provisions of Sharia Law (Study of Decision Number 1922/Pdt.G./2020/PA.Btm) - Puspitasari, Putri Mawardita; Wirdyaningsih, Wirdyaningsih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Cessie or what is known as Hawalah in Islamic financial institutions is a debt transfer agreement that is widelyused by banks because it is a way to transfer the right to collect to another party and/or a third party to guarantee creditfacilities or funds provided by the bank. In making a Deed of Cessie or Hawalah Deed, a Notary must pay attention to the provisions of positive law and Islamic law. This is related to legal certainty regarding the validity of the deed and itsharmony with Islamic law. The research method used in this study is the doctrinal research method. The data used in this study are secondary data obtained from document studies and strengthened by case analysis. The purpose of this study is to understand the legal consequences of a Hawalah Deed that does not meet the applicable legal provisions and the notary's responsibility for a Hawalah Deed that is canceled by a religious court. Based on the study’s result, a Hawalah Deed that does not meet the provisions of the law can be canceled or null and void by law. A Hawalah Deed that is canceled by the court makes the deed no longer have perfect evidentiary power. The notary who makes the deed can be sued for compensation, costs and interest in the aggrieved party.